(untitled) (Journal of Decision Science and Optimization, 2025)
The intersection of quantum theory and accounting presents an alternative way of understanding financial valuation and accounting practices. This paper applies quantum theory to cost accounting’s work-in-progress (WIP). WIP is conceptualized as in multiple states simultaneously, which provides probability amplitudes for different WIP values, and models interdependencies between various aspects of WIP. The study demonstrates how quantum concepts such as entanglement, superposition, measurement, teleportation , entropy , and tunnelling can be adapted to represent the dynamic nature of WIP. The primary contribution of this work is a more nuanced understanding of the uncertainties involved, which emerges by applying quantum phenomena to model the complexities and uncertainties inherent in managerial accounting. In contrast, previous works focus more on financial accounting or general accountancy.